Mechanisms of skeletal muscle atrophy in type 2 diabetes mellitus - Yang, Jingyi; Wang, Yingdong; Xu, Yuzhe; Jia, Xinqi; Lu, Fangping (Frontiers in Physiology, 2025)
IntroductionERS-induced apoptosis may play a pivotal role in diabetic skeletal muscle atrophy. However, the specific mechanisms by which ERS regulates skeletal muscle atrophy in diabetes remain unclear. The research examines the impact of endoplasmic reticulum stress (ERS) on skeletal muscle atrophy in type 2 diabetes mellitus (T2DM) mice.MethodsLeptin receptor-deficient Db/db mice (n = 7, 24-week-old, male) were employed as a type 2 diabetes model, while age-matched male C57BL/6J mice (n = 7) served as normal controls. Pathway enrichment analysis of differentially expressed genes was performed based on transcriptome sequencing data, focusing on apoptosis, ERS, and ubiquitin-proteasome pathways. Skeletal muscle morphology was assessed via anatomical observation, Laminin Staining, and immunoblotting analysis (WB). WB was used to detect ERS markers (ATF6, p-eIF2α, Bip, p-JNK, Chop), apoptosis-related proteins (Bcl2, Bax, Cleaved Caspase-3, CytC), p-Akt, and muscle atrophy marker Atrogin1.ResultsTranscriptomic enrichment analysis confirmed specific activation of apoptosis, ERS, and ubiquitin-proteasome pathways. WB revealed upregulated ERS-related proteins, increased apoptotic proteins, decreased p-Akt expression, elevated Atrogin1 levels, and enhanced proteolytic activity. Db/db mice exhibited significant skeletal muscle atrophy, with Laminin Staining demonstrating reduced cross-sectional area (CSA) of muscle fibers.DiscussionThese findings uncovers a dual regulatory mechanism underlying diabetic muscle atrophy. The diabetic skeletal muscle microenvironment exhibits elevated oxidative stress and significantly enhanced ER stress, which promotes direct muscle atrophy through ER stress sensor-mediated apoptosis. Concurrently, sustained ER stress suppresses Akt activity while upregulating the muscle-specific E3 ubiquitin ligase Atrogin1, thereby accelerating proteolysis and inducing indirect muscle wasting. These findings provide crucial mechanistic insights into diabetic skeletal myopathy, highlighting the ER stress signaling network as a promising therapeutic target for mitigating muscle atrophy in diabetes.